2021
DOI: 10.3390/ijms22158330
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of New Biodegradable Injectable Thermosensitive Smart Hydrogels for 5-Fluorouracil Delivery

Abstract: In this paper, injectable, thermosensitive smart hydrogel local drug delivery systems (LDDSs) releasing the model antitumour drug 5-fluorouracil (5-FU) were developed. The systems were based on biodegradable triblock copolymers synthesized via ring opening polymerization (ROP) of ε-caprolactone (CL) in the presence of poly(ethylene glycol) (PEG) and zirconium(IV) acetylacetonate (Zr(acac)4), as co-initiator and catalyst, respectively. The structure, molecular weight (Mn) and molecular weight distribution (Đ) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…These results indicate that Fickian diffusion plays a major role in the release process. It should be noted that smaller R² values were obtained with the Higuchi models [ 53 , 54 ], confirming that they are unsuitable release mechanisms for the studied MXene-Se-DOX nanocarriers ( Table S1 ).…”
Section: Resultsmentioning
confidence: 94%
“…These results indicate that Fickian diffusion plays a major role in the release process. It should be noted that smaller R² values were obtained with the Higuchi models [ 53 , 54 ], confirming that they are unsuitable release mechanisms for the studied MXene-Se-DOX nanocarriers ( Table S1 ).…”
Section: Resultsmentioning
confidence: 94%
“…The X -axis was wavenumber and Y -axis was the percent of transmittance. According to [ 42 ], the O-H stretch of hydrogen bond was ranged from 3500 to 3200 cm −1 , the C-O stretch 1260 to 1050 cm −1 , the C-H stretch from 3100 to 3000 cm −1 , and the C-C bond stretched around 1100 cm −1 . From Figure 5 , the functional group of ethanol was analyzed by using FTIR data.…”
Section: Resultsmentioning
confidence: 99%
“…Polyesters are one of the most significant groups of biodegradable polymers. Homo-, co-, and terpolymers of L-LA, rac -LA, CL, and Gly are widely employed in medicine, e.g., as drug carriers [ 3 , 6 , 39 ]. The advantage of DDSs over traditional drug forms is from controlled and sustained drug release in the body, which is influenced, among other things, by the microstructure of the chain [ 40 ] and the composition of the polymer carrier [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among other catalysts considered as non-toxic are Zn- and Zr- based compounds [ 3 ]. Our previous studies have shown that the polymers synthesized in the presence of diethylzinc [ 3 ] and zirconium(IV) acetylacetonate [ 6 ] may be considered as non-toxic in terms of cyto- and genotoxicity and thereby be suitable for pharmaceutical and medical applications.…”
Section: Introductionmentioning
confidence: 99%